Cell migration analysis: A low‐cost laboratory experiment for cell and developmental biology courses using keratocytes from fish scales. Issue 6 (19th June 2017) - Prieto, Daniel; Aparicio, Gonzalo; Sotelo‐Silveira, Jose R.
Abstract: Cell and developmental processes are complex, and profoundly dependent on spatial relationships that change over time. Innovative educational or teaching strategies are always needed to foster deep comprehension of these processes and their dynamic features. However, laboratory exercises in cell and developmental biology at the undergraduate level do not often take into account the time dimension. In this article, we provide a laboratory exercise focused in cell migration, aiming to stimulate thinking in time and space dimensions through a simplification of more complex processes occurring in cell or developmental biology. The use of open‐source tools for the analysis, as well as the whole package of raw results (available athttp://github.com/danielprieto/keratocyte ) make it suitable for its implementation in courses with very diverse budgets. Aiming to facilitate the student's transition from science‐students to science‐practitioners we propose an exercise of scientific thinking, and an evaluation method. This in turn is communicated here to facilitate the finding of common caveats and weaknesses in the process of producing simple scientific communications describing the results achieved. © 2017 by The International Union of Biochemistry and Molecular Biology, 45(6):475–482, 2017.